PEMANFAATAN MEDIA KREATIF UNTUK MENINGKATKAN INOVASI GURU DALAM PEMBELAJARAN DIGITAL MELALUI PELATIHAN CANVA DI UPT SMP NEGERI 4 TAKALAR - Zylfa Ummi Kalsum; Mutiara; Muhammad Nawir; Nasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital learning requires teachers to have the ability to innovate in developing creative and engaging learning media. This study aims to describe the use of creative media in improving teacher innovation in digital learning through Canva training at the UPT SMP Negeri 4 Takalar. The study used a descriptive qualitative approach with teachers who participated in the Canva training as subjects. Data collection techniques included observation, documentation of work results, and field notes during the activity. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the Canva training was able to improve creativity, digital literacy, and teacher confidence in designing visual-based learning media. Teachers were able to produce learning media in the form of posters, presentations, and digital infographics that were more engaging, interactive, and relevant to the teaching material. In addition, this training also encouraged a change in teachers' mindsets to be more adaptive to the use of technology in learning. Thus, the Canva training has proven effective in increasing teacher innovation in digital learning and needs to be implemented continuously to support the development of teacher professional competence.